Desmopressin Test in Silent Corticothoph Pituitary Adenomas, a Preliminary Study - a Comparison With Cushing Disease - Huayllas, Martha Katherine (J Endocr Soc, 2021)
Introduction: Silent corticothop adenomas (SCAs) account for 9 to 19% of nonfunctioning pituitary adenomas and behave as the most agressive pituitary tumors with more invasiveness and high recurrence rate. The identification of these patients during the preoperative stage could predict better surgery results. Some authors refer to high basal ACTH level in the preoperative evaluation as the only marker but until this date, there are no clinical and hormonal markers that could predict its occurrence. The aim of this study is to evaluate the response to desmopressin test and the presence of silent corticothoph tumors. Patients and Methods: Among 496 patients underwent pituitary surgery, 425 were pituitary adenomas, (106 were acromegaly, 46 Cushing disease, 10 prolactinomas, 263 nonfunctioning adenomas). Twenty-three patients, 17 with Cushing disease, (CD), mean age: 31 y, 13 female and 4 male) and 6 patients with SCA (mean age: 47 y, 5 female and 1 male) had positive ACTH confirmed by immunohistochemical analysis. Clinical characteristics: in the CD group, 53% had hypertension (9/17), 42% diabetes (7/17), 100% dyslipidemia, BMI was 30.7 kg/m(2). Among SCA group, 67% hypertension, 50% diabetes, 50% dyslipidemia, BMI was 28 kg/m(2). All patients were evaluated with basal ACTH and DHEAS before surgery. Patients with SCA underwent desmopressin test and were compared to CD. Dexamethasone suppression test (DST 1 mg) and 24-hour free urinary test was performed in patients with CD and in two patients with SCA. Response to desmopressin test was considered positive when increase in cortisol was above 20% and in ACTH of 35% using chemiluminescence assay (Immulite 2000). Results: Among CD group, the median (med) basal ACTH was 75.9 pg/mL (30.9 to 211), the med basal cortisol was 22.5 µg/dL (14.5 to 43.5), the med DHEAS was 170 µg/dL (33 to 465), the med 24h urinary free cortisol of 454.5 µg/24 h (149 to 1673) and med basal cortisol after DST 1mg of 15.4 µg/dL (4.7 to 31.5). Among SCA, med basal ACTH was 19.4 pg/mL (9.5 to 65.5), the med basal cortisol was 9.5 µg/dL (7.8 to 16.4) and the med DHEAS was 104.5 µg/dL (82 to 127). Only 4 patients with CD had macroadenomas. All of them responded with ACTH increase (med increase of 98%, 31.6 to 377%), and only 4 did not respond to cortisol increase (med increase of 54.4%, 0 to 167%). All patients with SCA had macroadenomas. Only one patient did not respond to ACTH increase (med increase of 123.5%, 9.5 to 1522%, 9.5 to 1522%), and 3 patients did not respond to cortisol increase (med increase of 17.9%, 0 to 234%). Discussion: SCA are invasive tumors, with high recurrence and tests predicting their occurrence are missing. We hypothesized that as ACTH is present in the adenoma a response to desmopressin test could exist (like CRH). Conclusion:The desmopressin test can be a useful tool in the evaluation of SCA and can predict pathological phenotype in preoperative tumors.